The Determinant of The Improvement of Sales Volume by Small Medium Enterprises That Sell Processed Food in Gorontalo Regency - Idris Yanto Niode; Raflin Hinelo (Journal of the Community Development in Asia (JCDA), 2020)
The study aims to determine the effect of partially or simultaneously the brand image of SMI products, investment through government capital assistance and zakat routines to increase the sales volume of IKM food processed products in Gorontalo Regency. The results showed (1) Simultaneously the brand image of IKM products, investment through government capital assistance and zakat routines simultaneously had a significant effect on the increase in sales volume of IKM food processed products in Gorontalo Regency. (2) partially brand image has a significant positive effect on the increase in sales volume of SMI food processed products in Gorontalo Regency. Investment through government capital assistance has not a significant positive effect on the increase in the sales volume of SMI food processed products in Gorontalo Regency. Zakat routine has a significant positive effect on the increase in the sales volume of SMI processed food products in Gorontalo Regency.